Risk Profile and Semi Quantitative Risk Probability of Aflatoxin B1 from Aspergillus flavus in a Dried Salted Fish in Several Regions of Java - Hidayah, Izhamil; Hermana, Irma; Kusmarwati, Arifah (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2018)
This study presents a semi-quantitative risk analysis, which determines the probability of aflatoxin B1 exposure from Aspergillus flavus in dried salted fish from the results of research conducted by Indriati about the prevalence of aflatoxin B1 in commercial dried fish from some regions of Java. Samples were randomly collected from retailers in Java, such as Banten, DKI Jakarta, West Java, Central Java and East Java, to obtain an approximate level of aflatoxin B1 exposure into Indonesian consumers. The occurrence of the probability of aflatoxin B1 risk from Aspergillus flavus was calculated by statistical, probability approach in @risk version 7.0 software with Monte Carlo simulation. The results of this study showed that the consumption of salted fish was about 3.7 g/capita/day. Hence there are risks of 7.74 cfu/g A. flavus exposure and 0.7291 ppb aflatoxin B1 exposure in 1 g of a salted fish taken from sampling locations. However this value is still categorized as low risk level.